Post a New Question

Math - Inverse Functions

posted by on .

Find the inverses of the following functions.

y = 3(x - 1)^2, x >= 1


Work:

x = 3(y - 1)^2
x = 3(y - 1)(y - 1)
x = 3(y^2 - y - y + 1)
x = 3y^2 - 6y + 3

And now what do I do!? Please explain and show me how to solve this inverse function!

...
Thank you

  • Math - Inverse Functions - ,

    x = 3(y - 1)^2 would be the inverse but you forgot the second part, y>=1

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question